EFL students’ readiness to have online learning during the Covid-19 pandemic among undergraduate students - Oktavia, Sherly Nanda; Hartono, Hartono; Widiyati, Elok; Hidayati, Nani (EduLite: Journal of English Education, Literature and Culture, 2023)
This study aimed to analyze the readiness levels of EFL students of the even semester of the English Education Study Program of Sultan Agung Islamic University to have online learning. This research was a descriptive study with a quantitative approach. The method used was a survey method. The data were collected through a closed-ended questionnaire. Ninety-seven English Education Study Program students in the academic year 2021/2022 participated in this research. It was found that computer and internet literacy had a mean of 25.53, which was moderate. While self-directed learning was at a low level with a mean of 24.74, and motivation of learning was also at a low level with a mean of 24.41. It means that the students could use computers, laptops, and smartphones to complete course assessment tasks and facilities available on campus. It reported that students could not manage difficulty to present high performance on online learning to work independently. Besides computer and internet literacy and self-directed learning, motivation to learn was another factor that affected students' readiness. It found that during Covid-19, many students did not have high motivation to learn.